Är det svårt att använda ordlistor som är utarbetade enligt terminologiska principer? Begreppsanalysens fördelar och nackdelar - Kalliokuusi, Virpi (Nordiske Studier i Leksikografi, 1997)
The vocabularies and glossaries compiled by Tekniikan Sanastokeskus (fSK, The Finnish Centre for Technical Terminology) are based on applied theories ofterminology and they include terms and definitions for concepts of various fields of specialised knowledge. Although, quite often, these vocabularies have been praised by the users for being clear, systematic, thorough and thus reliable, they have also been critized. In my presentation, I will discuss some reasons for such a criticism and try to see how the difficulties faced by the users could be resolved when structuring knowledge related to concepts. As most of the criticism results, directly or indirectly from the methodology itself, I will begin the presentation with a short overview of the terminological priciples and methods that underpin the practical compilation of TSK's vocabularies and terminological glossaries in general. Knowledge and awareness ofthese principles will help us understand why these vocabularies have a certain appearance and structure and why the various practical solutions should be carefully selected in accordance with the methodological basis.